Reaction of Phthalic Anhydride and Ethylenediamine - Zhang, Qun-Zheng; Li, Chang-Chun; Gu, Xue-Fan; Yang, Peng-Hui; Zhang, Xunli (Asian Journal of Chemistry, 2011)
The reactions of phthalic anhydride and ethylenediamine were performed and the effect of solvents was investigated with a wide range of solvents in two groups (either containing H2O or without H2O). In H2O-containing media, phthalic ethylene ammonium salt was obtained with high yields; when the reaction was carried out in non-aqueous solvents, N,N'-diphthaloyl-1,2-ethylenediamine was formed at lower reaction rates and yields. All products were characterised and confirmed by a combination of analytical techniques. The use of water as solvent with a reasonably high product yield (80 %) suggests a green route for the synthesis of phthalic ethylene ammonium salts.